Kemurahan Hati dalam Bingkai Kasih Kristus: Analisa Historis Kritis Roma 12:20 - Sianipar, Ronald; Tetelepta, Hendrik Bernadus; Harefa, Otieli; Paat, Vicky BGD (ELEOS: Jurnal Teologi dan Pendidikan Agama Kristen, 2025)
Abstract: This study aims to present the hermeneutics of Romans 12:20 concerning Paul's teaching to the Roman church about loving one's enemies. The research highlights the thematic shift in Romans 12, from the doctrinal discussions in the previous eleven chapters to the implementation of doctrine in daily life, with an emphasis on attitudes toward others, including enemies, in the context of the socio-political tensions in Rome at that time. The author employs the historical-critical hermeneutical method to analyze key terms in Romans 12 and the book of Romans, while also considering the socio-political context of the time. The findings of this study reveal that Romans 12:20 parallels Proverbs 25:21-22, reflecting the influence of Jewish tradition in Paul's teaching about loving enemies. This concept is highly relevant in the context of the complex social, political, and religious pluralism in Rome, underscoring the importance of theological and ethical guidance in Christian life. These findings also offer insights for applying the principle of loving enemies in the context of the contemporary church and Christian society, serving as a guide in addressing similar social and political tensions. Abstrak: Kajian ini bertujuan untuk mempresentasikan hermeneutika Roma 12:20 mengenai pengajaran Paulus kepada jemaat Roma tentang mengasihi musuh. Penelitian ini menyoroti pergeseran tema dalam teks Roma 12, dari doktrin yang dibahas dalam 11 pasal sebelumnya, ke implementasi doktrin dalam kehidupan sehari-hari, dengan penekanan pada sikap terhadap sesama, termasuk musuh, dalam konteks ketegangan sosial-politik Roma pada masa itu. Penulis menggunakan metode hermeneutika historis-kritis untuk menganalisis kata kunci dalam perikop Roma 12 dan kitab Roma, serta memperhatikan konteks sosial-politik pada waktu itu. Hasil penelitian ini menunjukkan bahwa Roma 12:20 memiliki paralel dengan Amsal 25:21-22, yang mencerminkan pengaruh tradisi Yahudi dalam pengajaran Paulus tentang mengasihi musuh. Konsep ini sangat relevan dalam konteks kompleksitas struktur sosial, politik, dan pluralitas agama di Roma, serta menekankan pentingnya panduan teologis dan etika dalam kehidupan Kristen. Temuan ini juga memberikan wawasan bagi penerapan prinsip mengasihi musuh dalam konteks gereja dan masyarakat Kristen masa kini, sebagai pedoman dalam menghadapi ketegangan sosial dan politik yang serupa.